Family weight management in rural U.S. communities: a mixed methods study of parent and child perspectives - Alyssa Button; Denise Holston; Jamila Freightman; Katherine Seals; Matthew Helie; Elizabeth Bankhead; Deirdre Harrington; Peyton Murray; Amanda Staiano (BMC Public Health)
Abstract Background Effective treatments are available to address the rising prevalence of childhood obesity in the U.S. Families in rural communities face unique barriers to accessing and engaging in these programs. This study evaluated interests and considerations for behavioral health programming to treat child obesity in rural southern U.S. Methods Rural counties with high prevalence of adult obesity (> 40%) were selected for recruitment following interviews with community partners and agents, in accordance with the Hexagon Tool framework. Researchers collaborated with extension agents and communities to recruit parents (n = 33) and children (n = 15) for cross-sectional focus groups and parent surveys (n = 295). The survey was adapted from questions on The Knowledge, Attitudes and Practices Scale, The Behavioral Information Preference Scale, and The Health Information National Trends Survey. Parent focus group data was analyzed using inductive reasoning, and content analysis was used for child focus group data. Descriptive statistics were used to interpret survey results. Results Parent surveys (18–54 years, 50% male) indicated concern for childhood overweight and obesity (129/295 responses), as well as great interest in health education (153/295). Responses indicated high acceptability of digital (184–193/295) and group-class (192/295) formats for programming and accessing information. During focus groups, parents (≥ 18 years, 94% female) identified structural barriers including lack of resources as limitations for participation. Children (M = 10.5 ± 1.3 years, 60% boys) identified improving overall health and athleticism as desired outcomes. Conclusions Families living in rural settings desire programming for childhood obesity treatment. Researchers and community leaders can build capacity and utilize existing resources to implement programs.